Strategi Pembelajaran Aktif Question Student Have (QSH) Pada Mata Pelajaran Fiqh di MTs Negeri 9 Bantul - Ida Zusnani; Ali Murfi (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan, 2020)
Learning that does not pay attention to individual differences in children and is based on the wishes of the teacher, will be challenging to be able to lead students towards the achievement of learning goals. One application rather than active learning is the Question Students Have strategy (questions from students). This study aims to find out and understand the forms, steps, strengths, and weaknesses of the Question Student Have (QSH) learning strategy, as well as how the Learning Implementation Plan (RPP) is modeled in Fiqh subjects in MTs Negeri 9 Bantul. This research uses a qualitative descriptive method. The results showed that the form of the Question Student Have strategy teachers stimulated students to learn firsthand the learning material materials that would be delivered within a specific time. After that, students are invited to submit questions from material that they do not understand nor understand. Steps to make the Question Student Have strategy more effective then allocate time for each session after that if the class is too large so that there is not enough time to distribute the paper to all students, divide the class into groups and follow the instructions as above. This Question Student Have a strategy that can attract and focus the student's attention even though the classroom situation was complicated before or students had a joking habit during the lesson. However, not all students were comfortable with making questions because the level of students' abilities in the class was different. In the future, a teacher must continue to look for and formulate strategies that can embrace all differences held by students. Keywords: Active Learning Strategies, Question Student Have (QSH), Fiqh Subjects, MTs Negeri 9 Bantul.